Review of Nondestructive Testing (NDT) Techniques for Timber Structures - Ziad Azzi; Houssam Al Sayegh; Omar Metwally; Mohamed Eissa (Infrastructures)
The widespread adoption of wood in construction is driven by its sustainability, cost-effectiveness, and esthetic appeal. The construction of wood buildings often requires minimal specialized equipment, contributing to affordability and higher demand for wood-frame structures. Wood is considered more sustainable than other building materials, such as steel or concrete, for several reasons, including its renewable nature, low embodied energy, carbon sequestration, energy efficiency, and biodegradability, among others. In the United States, wood is the most common material used in building construction. While many of the structures are single-family homes, wood framing is also prevalent in larger apartment complexes, as well as commercial and industrial buildings. Timber has also been traditionally used for bridge construction, and recently, it has been considered again for the construction of new bridges. Over time, wood-frame construction has developed from a basic method for primitive shelters into a sophisticated field of structural design. As an eco-friendly resource, wood is crucial for promoting sustainable building practices. However, ensuring the long-term performance and safety of timber structures is essential. Regular inspections and testing of wooden structures are important to identify signs of wear, damage, or decay. One type of testing which is gaining popularity is nondestructive testing (NDT). NDT techniques have become invaluable for assessing the condition of timber components because such techniques are non-invasive in nature and do not cause damage, ensuring that structures remain functional with minimal disruptions. These methods provide critical insights into the structural integrity and operational efficiency of wood under sustained loads and in inclement environments. This article examines various NDT techniques used to evaluate timber structures, highlighting their capabilities, as well as advantages and limitations. It also discusses the importance of wood in advancing sustainability within the construction industry and emphasizes the need for accurate and reliable assessment methods to enhance the use of timber as an environmentally friendly building material. By incorporating NDT practices into regular inspection and maintenance protocols for buildings, bridges, and other structures, various stakeholders can ensure the durability, longevity, and safety of timber structures, thereby contributing to the progress and advancement of sustainable construction practices worldwide.